2018
DOI: 10.1002/aocs.12034
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Solution Cast Films From Pennycress Protein Isolate

Abstract: This research evaluated a value-added use of pennycress protein by producing films and determining their properties. Pennycress (Thlaspi arvense L.) grows over the winter months, and is harvested in the spring. Pennycress seeds have high oil content and are a good candidate for biodiesel production. In order to extract the most value from pennycress, all parts of the seed must be utilized. An improved pilot-plant method for extracting protein from pennycress was developed providing a pennycress protein isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Researchers at USDA ARS in Peoria, Illinois, developed extraction methods producing 90%–97% crude protein successfully from wild‐type pennycress (Hojilla‐Evangelista et al., 2013, 2014, 2015). The extracted pennycress protein compared well with soybean/canola protein attributes with excellent emulsifying, foaming, and water‐holding capacities validated by another independent research effort (Hojilla‐Evangelista et al., 2023; Selling et al., 2018). Using advanced genomics and a translational approach, CoverCress pennycress was developed by private industry with low fiber, high protein, and high oil pennycress cultivars using TTG1 or TT8 mutant lines (Hartnell et al., 2022).…”
Section: Trait Improvement Effortsmentioning
confidence: 68%
See 1 more Smart Citation
“…Researchers at USDA ARS in Peoria, Illinois, developed extraction methods producing 90%–97% crude protein successfully from wild‐type pennycress (Hojilla‐Evangelista et al., 2013, 2014, 2015). The extracted pennycress protein compared well with soybean/canola protein attributes with excellent emulsifying, foaming, and water‐holding capacities validated by another independent research effort (Hojilla‐Evangelista et al., 2023; Selling et al., 2018). Using advanced genomics and a translational approach, CoverCress pennycress was developed by private industry with low fiber, high protein, and high oil pennycress cultivars using TTG1 or TT8 mutant lines (Hartnell et al., 2022).…”
Section: Trait Improvement Effortsmentioning
confidence: 68%
“…Researchers at USDA ARS in Peoria, Illinois, developed extraction methods producing 90%-97% crude protein successfully from wild-type pennycress (Hojilla-Evangelista et al, 2013, 2014. The extracted pennycress protein compared well with soybean/canola protein attributes with excellent emulsifying, foaming, and waterholding capacities validated by another independent research effort (Hojilla-Evangelista et al, 2023;Selling et al, 2018).…”
Section: Seed Protein Compositionmentioning
confidence: 77%
“…They reported that, depending on the extraction method (saline‐based or conventional acid precipitation), WTP protein isolates were highly soluble (at least 76% soluble proteins) from pH 2 to 10, showed excellent foaming and emulsifying properties, and had high water‐holding capacities. Selling et al (2018) recently used WTP protein isolates to produce smooth and defect‐free cast films with low water vapor and oxygen permeability. These findings demonstrated that WTP protein may be used as an alternative protein source in pressurized or whipped foam products, emulsions, films, and other products in the rapidly expanding plant‐based protein market.…”
Section: Introductionmentioning
confidence: 99%